2021
DOI: 10.1002/aic.17349
|View full text |Cite
|
Sign up to set email alerts
|

H2SO4‐catalyzed isobutane alkylation under low temperatures promoted by long‐alkyl‐chain surfactant additives

Abstract: To deeply understand the role of surfactants on the acid/C4 hydrocarbon miscibility, the catalytic activity and molecular‐level interfacial properties of long‐alkyl‐chain cationic surfactants (hexadecyltrimethylammonium bromide, CATB and dihexadecyldimethylammoniumchloride, DDAB) and anionic one (sodium dodecyl benzene sulfonate, SDBS) were studied as additives for H2SO4 alkylation using experiments and molecular dynamics simulations. Surfactant additives are found to efficiently decrease by‐products and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…It is well-confirmed that surfactants as the additives of H 2 SO 4 alkylation can efficiently enhance the quality of alkylate 15,16 . Chen et al reported several cationic, anionic, and amphoteric surfactants as additives in C4 alkylation in 2003 17 .…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…It is well-confirmed that surfactants as the additives of H 2 SO 4 alkylation can efficiently enhance the quality of alkylate 15,16 . Chen et al reported several cationic, anionic, and amphoteric surfactants as additives in C4 alkylation in 2003 17 .…”
Section: Introductionmentioning
confidence: 88%
“…At last, 6 ns NVT was carried out for data collection of interest with the time steps of 2.0 fs. The semi-isotropic Parrinello Rahman barostat method on z axis was used with 2.0 ps relaxation time at 1 bar for all the NPT ensemble to keep the interface unchanged 15 .…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations